PERSEPSI WANITA TANI SUKU BUGIS DAN SUKU JAWA DAN HUBUNGANNYA DENGAN PERANAN DALAM PEMBIBITAN MANGROVE UNTUK PENINGKATAN PENDAPATAN KELUARGA DI DESA SIDODADI KECAMATAN PADANG CERMIN KABUPATEN LAMPUNG SELATAN - Gultom, Dame Trully; Aviati S, Yuniar (Lampung University)
The objectives of the research were to study (1) The perception of Javanese and Bugis women worken mangrove nursery (2) The role of javanese and Bugis women worker in mangrove nursery (3) Factors related to the role of javanese and Bugis women worker in mangrove nursery. The research was conducted using servey method in Sidodadi village, Padang Cermin Sub Distric Central, South Lampung District. The samples were 38 people which is 13 people of Bugis women worker and 25people Javanese women worker. The data collected were analyzed descriptively and statistically using Rank Spearman Correlation. The study showed that : (1) There is the same perception of Javanese and Bugis women worker in mangrove nursery. (2) The role for Bugis women is 14,88 HKP and 17,72 HKP for Javanese women. (3) There were correlation between age, household task, members family with the role of Javanese and Bugis women worked in mangrove nursery. There were no correlation between total income, education, distane and amount of under five years kid with the role of Javanese and Bugis women worked in mangrove nursery.